Juno/JEDI observations of 0.01 to >10 MeV energetic ions in the Jovian auroral regions: Anticipating a source for polar X‐ray emission - D. K. Haggerty; B. H. Mauk; C. P. Paranicas; G. Clark; P. Kollmann; A. M. Rymer; S. J. Bolton; J. E. P. Connerney; S. M. Levin (Geophysical Research Letters)
Abstract After a successful orbit insertion, the Juno spacecraft completed its first 53.5 day orbit and entered a very low altitude perijove with the full scientific payload operational for the first time on 27 August 2016. The Jupiter Energetic particle Detector Instrument measured ions and electrons over the auroral regions and through closest approach, with ions measured from ~0.01 to >10 MeV, depending on species. This report focuses on the composition of the energetic ions observed during the first perijove of the Juno mission. Of particular interest are the ions that precipitate from the magnetosphere onto the polar atmosphere and ions that are accelerated locally by Jupiter's powerful auroral processes. We report preliminary findings on the spatial variations, species, including energy and pitch angle distributions throughout the prime science region during the first orbit of the Juno mission. The prime motivation for this work was to examine the heavy ions that are thought to be responsible for the observed polar X‐rays. Jupiter Energetic particle Detector Instrument (JEDI) did observe precipitating heavy ions with energies >10 MeV, but for this perijove the intensities were far below those needed to account for previously observed polar X‐ray emissions. During this survey we also found an unusual signal of ions between oxygen and sulfur. We include here a report on what appears to be a transitory observation of magnesium, or possibly sodium, at MeV energies through closest approach.